Aplastic Anemia Treated with Eltrombopag during Pregnancy - Yuri Suminaga; Yoshitsugu Chigusa; Tadakazu Kondo; Haruko Okamoto; Yosuke Kawamura; Mana Taki; Masaki Mandai; Haruta Mogami (Hindawi Limited, 2022)
Aplastic anemia is a rare blood disorder characterized by pancytopenia and hypocellular bone marrow. In patients with aplastic anemia, pancytopenia sometimes worsens during pregnancy, and relapse of aplastic anemia in pregnancy is common. Nevertheless, only supportive care with blood products is the mainstay of treatment of aplastic anemia in pregnancy. Thus, the obstetric management and treatment of aplastic anemia in pregnancy is extremely challenging. We herein report the first case of a pregnant woman complicated with aplastic anemia who was successfully treated with eltrombopag, a thrombopoietin receptor agonist. A 27-year-old primigravida woman who had a history of aplastic anemia refractory to immunosuppressive therapy and was treated with eltrombopag became pregnant. Eltrombopag treatment was continued after weighing the benefits and potential risks. Throughout pregnancy, the woman's pancytopenia did not progress, and she delivered a 2336 g baby vaginally at 38 weeks of gestation. Her postpartum outcome was uneventful, and the neonate did not develop thrombocytosis. Since the efficacy and safety of eltrombopag in pregnancy has not yet been established, its routine use should be avoided. However, if limited to refractory cases and with adequate maternal and fetal monitoring, including neonatal blood examinations, the use of eltrombopag for patients with aplastic anemia during pregnancy may be acceptable and result in favorable maternal and fetal outcomes.